Analisa Certainty Factor Dalam Mendiagnosa Kerusakan Alat Pemancar Radio 87.6 Dass FM Lubuk Pakam - Harry Sutanto; Bosker Sinaga (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2020)
An FM transmitter or FM transmitter is a source of radio vibrations emitted by a device called an oscillator or oscillator. While the oscillator is a device that can produce high frequencies. The scope of this research is an expert system that is built only to discuss the symptoms and damage to radio transmitters and solutions to fix them. The resulting output is radio transmitter malfunction information and solutions to repair it. The programming language used in solving this problem is PHP by using the mysql database. The method used in solving the damage to the radio transmitter is the certainty factor method.